2001
DOI: 10.1113/eph8602090
|View full text |Cite
|
Sign up to set email alerts
|

The Contribution of Chemoreflex Drives to Resting Breathing in Man

Abstract: _1), and compared it to ventilation at rest (mean ± S.E.M. = 9.1 ± 0.7 l min _1 ). The difference was significant (Student's paired t test, P < 0.001). We also considered the threshold P CO 2 observed during rebreathing to be an estimate of the chemoreflex threshold at rest (mean ± S.E.M. = 42.0 ± 0.5 mmHg). However, P ET,CO 2 during rebreathing estimates mixed venous or tissue P CO 2 , whereas the resting P ET,CO 2 during resting breathing estimates P a,CO 2 (arterial partial pressure of carbon dioxide). The … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
20
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(22 citation statements)
references
References 23 publications
2
20
0
Order By: Relevance
“…The values that were obtained for the chemoreflex ventilation threshold and sensitivity in the current research are similar to those our laboratory reported previously (Mahamed et al 2001). Results regarding the effect of training on the chemoreflex ventilation threshold obtained during rebreathing have not been reported previously in the literature.…”
Section: Chemoreflex Responsesupporting
confidence: 70%
“…The values that were obtained for the chemoreflex ventilation threshold and sensitivity in the current research are similar to those our laboratory reported previously (Mahamed et al 2001). Results regarding the effect of training on the chemoreflex ventilation threshold obtained during rebreathing have not been reported previously in the literature.…”
Section: Chemoreflex Responsesupporting
confidence: 70%
“…Although the use of respiratory equilibrium diagram has been described by Mahamed et al (2001), there is no report of experimental study in humans that quantitatively validates the major mechanism of exercise hyperpnea based on integration of the controller and plant properties in the respiratory equilibrium diagram.…”
Section: Introductionmentioning
confidence: 98%
“…1B), quantitative analysis of both subsystems can determine how changes in both the controller and plant elements affect V E or Pa CO 2 (5,6,17,18,41,45,46,48); however, to what extent changes in central blood volume (CBV) influence these variables and thus, by consequence, the operating point (V E or Pa CO 2 response) of the respiratory control system remain unclear.…”
mentioning
confidence: 99%
“…It can be divided into two subsystems (Fig. 1A): a controller (controlling element) and a plant (controlled element) (5,17,18,21,35,41,45,46).Recently, we have characterized these subsystem elements in an open-loop condition and constructed a respiratory equilibrium diagram to illustrate the mechanisms of respiratory control at rest and during exercise in endurance-trained and untrained subjects (46,48,52). Briefly, the controller element approximates a straight line where minute ventilation (V E) increases as a function of Pa CO 2 .…”
mentioning
confidence: 99%